Ethical Consumption amongst Chinese Students (In UK): An Empirical Study on Ethical Consumption Issues - WU, YX (2013)
Abstract This paper aims to explore the ethical consumption issues among the overseas Chinese students in UK. In other words, this paper attempts to gain an understanding of the factors or motivations that drive Chinese students to consume ethically or reject to do so. The research conducted used qualitative research method (semi-structured interview) on 12 Chinese students study at Business School in University of Nottingham. The collected data from the researched Chinese students indicated that Chinese students who consume ethically influenced by their cultural and personal characteristics, ethnical background, as well as their pursuit of distinctive life style and opportunities to demonstrate their love. Further, this research revealed that Chinese student who consume unethically oriented by their social norms and traditions, ethical unconscious and three common justifications (e.g. economic rationalism, institutional dependency and development realism). Further, the results of the research can offer the potential for both scholars and practitioners and fulfil the gap between the current ethical consumption study and uncovered consumer groups in some way. However, the results of this research can be hardly generalised due to the constraint of sample unit, sample size and single research method. Hence, for the purpose of future research, sample unit, sample size and selection of research method should be improved accordingly.